Wetting of h-BN by molten Cu-8.8Zr-xTi ternary alloys at 1373 K. (March 2020) - Lin, Qiaoli; Wang, Le; Sui, Ran; Sharif, Muhammad Haroon
Abstract: The wetting of hexagonal boron nitride (h-BN) by molten Cu–Zr eutectic alloy with different Ti concentration (0-10 at.%) was studies by a modified sessile drop method at 1373 K under high vacuum. h-BN cannot be wetted by Cu–Zr eutectic alloy (equilibrium contact angle is ~128°), but a small addition of Ti (2.5 at.%) can decrease contact angle significantly. Interfacial reaction products Ti-nitride, Ti-diboride, Zr-nitride and Zr-diboride were observed and identified using SEM and XRD. The reason of contact angle decreasing with Ti concentration in wetting case of Cu-8.8Zr- x Ti ( x  = 2.5, 7.5, 10) system is the reducing of stoichiometry of TiN y, which makes TiN y has a better metallic property. In addition, the adsorption of Ti at liquid/solid interface is not a negligible factor. In non-wetting cases of Cu-8.8Zr and Cu–10Ti, the negative molar exchange energy values between Cu–Zr and Cu–Ti indicate Zr and Ti would be attracted by the bulk of liquid. Thereby, the improvement in the wettability of h-BN by Cu–Zr and Cu–Ti binary alloys is very limited. Highlights: Wettability of Cu-8.8Zr- x Ti is better than Cu–Zr and Cu–Ti on h-BN. Nitrides take precedence over borides in interfacial precipitation phases. Both TiN x and adsorption of Ti at interface induce the better wettability.